NEGLECT OF CHILD CUSTODY RIGHTS POST JUDGMENT (AN ANALYSIS OF THE ROLE OF THE SIGLI SHARIA COURT) - Miftahul Jannah; Muliadi Kurdi; Irwansyah Irwansyah (JURNAL HAKAM, 2026)
Divorce rulings often result in a battle for child custody, driven merely by a desire to satisfy a momentary ego, and consequently fail to grant the child their rightful custody. This study examines the phenomenon of the neglect of custody rights (child custody) that occurs following a final legal ruling by the Sigli Sharia Court. This study employs a qualitative approach using an empirical legal research methodology. Data were collected through in-depth interviews, observation, documentation and document analysis. The data were subsequently analysed and presented qualitatively. The findings indicate that the neglect of custody rights is driven by the parents’ self-interest, a lack of understanding regarding the enforceability of the ruling, and psychological barriers faced by the child. The role of the Sigli Sharia Court in addressing this issue includes post-judgment mediation efforts and the implementation of actual enforcement. The court adopts a passive stance and cannot carry out active supervision without a request from the parties involved. However, it was found that the enforcement of custody rights often reaches an impasse due to its personal and sensitive nature, thus requiring stronger coordination with child protection agencies and other law enforcement authorities. This study concludes that strengthening the functions of oversight and legal education for the community in Pidie Regency is crucial to safeguarding the best interests of the child, alongside optimal coordination between the DP3A/P2TP2A, village officials and child protection agencies in ensuring that custody rights are upheld.